Use of the clayey cover of bauxite deposits of the Amazon region for geopolymer synthesis and its application in red ceramics. (20th September 2021) - Barreto, Igor Alexandre Rocha; Costa, Marcondes Lima da
Highlights: The predominance of kaolinite in the sample contributes to its application in geopolymer synthesis. The best synthesis parameters were determined through Box-Behnken design: 3.4–3.8Si/Al, 1–1.1Na/Al, and temperature of 100 °C. Mechanical strength of up to 47.78 MPa was obtained by geopolymers. Immersion in water for 24 h does not affect the mechanical strength of the geopolymers. Abstract: The exploitation of bauxite deposits in the Amazon region is well known. Mining begins with the temporary or even permanent removal of an extensive surface layer of clayey material (Belterra clay) that can reach a thickness of up to 20 m. The mineralogical composition of this material has already been described in the literature and consists mainly of kaolinite. The extensive surface distribution of Belterra clay in the Amazon region and its composition is of interest in the evaluation of its viability for the synthesis of geopolymers. For the present study, a sample of Belterra clay (BTC-1) from the bauxite deposits of Rondon do Pará was selected, in addition to microsilica (MCR-1) (Ecopowder) and Sigma P.A. reagent (NaOH). The Belterra clay sample was characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF), and thermogravimetric (TG) and differential scanning calorimetry (DSC) analyses. To determine the physical and mechanical properties of Belterra clay, geopolymers were synthesized using BTC-1, MCR-1, and NaOH with different Si/Al and Na/Al ratios according to the Box-Behnken design (BBD). Technological tests, including water absorption, apparent porosity, and compressive strength tests, were performed. Based on the BBD, the highest compressive strength was 47.78 MPa, and the lowest compressive strength was 7.05 MPa. BTC-1 showed potential for the synthesis of geopolymers with high mechanical strength and an acceptable percentage of water absorption.